Workplace health promotion in Poland in 2015 - Diagnosis based on a representative survey of companies employing more than 50 employees - Krzysztof Puchalski; Elżbieta Korzeniowska (Nofer Institute of Occupational Medicine, 2017)
Background: The workplace health promotion (WHP) activity of enterprises in Poland was examined. The findings referred to how many companies implemented non-obligatory actions for health and what actions were taken, what were the reasons and obstacles in the implementation, whether companies evaluated their activity, how they motivated staff to WHP, and whether the size and economic standing differentiated their activity. Material and Methods: Representative survey, consisted of computer assisted telephone interviews with delegates of the boards of 1000 companies employing > 50 employees, held in November-December 2015. Results: Every second company undertook voluntary actions for workers health. Most often they offered medical care, supported physical activity and took care about the work environment in a higher range than required by binding regulations. They promoted health to build company's good image, improve productivity and reduce costs. The tradition of WHP in the company, attitudes of employers and intention to boost the vitality of employees also played a role . Despite good financial standing of companies, the shortage of funds was the main barrier in the implementation of WHP activities. Other impediments, such as lack of sufficient state incentives, workload of the management staff, lack of knowledge about WHP benefits and lack of good pro-health services were observed as well. Few companies motivated employees to WHP and carried out its evaluation. Conclusions: The development of WHP requires dissemination of its benefits among employers, human resources and safety personnel trainings in WHP management, implementation of the system of relief and prestigious awards for active companies, increase in the number and scope of research works on WHP conditions and effectiveness. Crucial herein is the role of the state in cooperation with other major WHP actors. Med Pr 2017;68(2):229-246